Dental age estimation methods in children based on radiograph panoramic - Shintya Rizki Ayu Agitha; Icha Artyas Annariswati (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2021)
Objectives: Age estimation is a key point in forensics, archeology, pediatrics and pediatric dentistry. Analysis using the development of teeth is one of the available methods that are used for physical identification, as well as age, in children. This article reviewed several journals about the methods of age identification, especially in children. The purpose of this review was to briefly inform about the recent researches regarding the application of age identification methods in children by using panoramic radiography as it is the most widely used method, in the years 2020-2021. Review: This article was a narrative review. Analyzed articles were searched from the PubMed database which were published between 2020 until 2021. There were 12 journals in accordance with the inclusion criteria of age estimation method in children using panoramic radiography. Conclusion: 7 of 12 journals that met the inclusion criteria used Willems method in the researches, 5 journals used Demirjian method, 3 journals used Cameriere method, 2 journals used Nolla method. Willems method was the most used analysis for identifying age and proved to be effective for identification in various populations, such as Belgium, Caucasian, Turkish, Saudi Arabian, Kenyan, Chinese and Taiwanese.